2016
DOI: 10.1371/journal.pone.0168959
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Characterization of Differential Abundant Proteins Accumulated between Lower and Upper Epidermises of Fleshy Scales in Onion (Allium cepa L.) Bulbs

Abstract: The onion (Allium cepa L.) is widely planted worldwide as a valuable vegetable crop. The scales of an onion bulb are a modified type of leaf. The one-layer-cell epidermis of onion scales is commonly used as a model experimental material in botany and molecular biology. The lower epidermis (LE) and upper epidermis (UE) of onion scales display obvious differences in microscopic structure, cell differentiation and pigment synthesis; however, associated proteomic differences are unclear. LE and UE can be easily sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Also, differences in UDP-arabinopyranose mutase 1-like protein and β-1,3-glucanase in the LE, may be related to the differences in cell sizes in LE and UE of red and yellow onions (Wu et al. 2016 ). It was also shown that onions contain allylsulfides and flavonoids including quercetin which exert antioxidative activities and could reduce hepatocytes apoptosis; also, onion contains steroid saponins and sapogenins, and β-chlorogenin which is a characteristic steroid sapogenin.…”
Section: Methodsmentioning
confidence: 99%
“…Also, differences in UDP-arabinopyranose mutase 1-like protein and β-1,3-glucanase in the LE, may be related to the differences in cell sizes in LE and UE of red and yellow onions (Wu et al. 2016 ). It was also shown that onions contain allylsulfides and flavonoids including quercetin which exert antioxidative activities and could reduce hepatocytes apoptosis; also, onion contains steroid saponins and sapogenins, and β-chlorogenin which is a characteristic steroid sapogenin.…”
Section: Methodsmentioning
confidence: 99%
“…2-DE and MS approaches identified 47 differential abundant protein spots between lower and upper epidermis of scales in red and yellow onions; among these, 31 were reported to be unique proteins. These differential proteins were involved in flavonoid synthesis, response to stress, and cell division ( Wu et al, 2016 ) . While studying gametogenesis and sterility in garlic, significant differences were observed in the 2-DE profile between sterile and fertile genotypes.…”
Section: Survey Methodologymentioning
confidence: 99%
“…[24] Scale epidermises of from yellow and red onion bulbs The abundance and enzymatic activity of β-1,3-glucanase were all higher in upper epidermis in both onions. [3] Imbibed sunflower seeds at 20 or 10°C 2DE-based; LC-MS/MS 105 DAPs, including 49 enzymes Ten enzymes by ABBP method Low concordance between enzyme abundance and activity. GAPDH, PGK, MDH, and AlaT increased in abundance at 20°C but showed low activity compared to 10°C.…”
Section: Mdh By Colorimetric Methodsmentioning
confidence: 99%
“…The interpretation and validation of proteomic data has always been a common concern in the proteomics community. [2][3][4] Once DAPs are identified in comparative proteomics, it is essential to confirm the change in their abundance, and their role in the biological process under scrutiny. Eukaryotic proteins generally have multiple independent functions, especially as enzymes.…”
Section: Doi: 101002/pmic201800234mentioning
confidence: 99%